A well-conserved Plasmodium falciparum var gene shows an unusual stage-specific transcript pattern. - Kyes, SA; Christodoulou, Z; Raza, A; Horrocks, P; Pinches, R; Rowe, J; Newbold, C (2003)
The var multicopy gene family encodes Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) variant antigens, which, through their ability to adhere to a variety of host receptors, are thought to be important virulence factors. The predominant expression of a single cytoadherent PfEMP1 type on an infected red blood cell, and the switching between different PfEMP1 types to evade host protective antibody responses, are processes thought to be controlled at the transcriptional level. Contradictory data have been published on the timing of var gene transcription. Reverse transcription-polymerase chain reaction (RT-PCR) data suggested that transcription of the predominant var gene occurs in the later (pigmented trophozoite) stages, whereas Northern blot data indicated such transcripts only in early (ring) stages. We investigated this discrepancy by Northern blot, with probes covering a diverse var gene repertoire. We confirm that almost all var transcript types were detected only in ring stages. However, one type, the well-conserved varCSA transcript, was present constitutively in different laboratory parasites and does not appear to undergo antigenic variation. Although varCSA has been shown to encode a chondroitin sulphate A (CSA)-binding PfEMP1, we find that the presence of full-length varCSA transcripts does not correlate with the CSA-binding phenotype.